Edukasi Politik dalam Pelaksanaan Pemilihan Kepala Daerah (Pilkada) Langsung Kabupaten Kampar Provinsi Riau Tahun 2017 - Candra Asmara (Laboratorium Jurusan Ilmu Pemerintahan FISIP Universitas Riau, 2018)
One area that implements direct Regional Head Election (Pilkada) in 2017, is Kampar Regency, Riau Province. The implementation of the Kampar Regency Direct Local Election has been running three times, namely in 2006, won by the pair Burhanudin Husein and Teguh Sahono; The 2011 regional election was won by Jefry Noer and Ibrahim Ali and the latest direct election was in 2017 which was won by elected regent Aziz Zainal and Catur Sugeng Santoso. This research study focused on analyzing political education in the implementation of Direct Regional Head Elections (KILKADA) in Kampar Regency in 2017 and knowing the Barriers found in realizing political education for the community at the time of Direct Election of Regional Heads (PILKADA) in Kampar District in 2017. This type of research is to use a type of qualitative research. According to Moleong (1999: 23) said that qualitative research methods basically use an inductive approach, ie data is collected, analyzed, abstracted and theories will emerge as qualitative discoveries. In this research, it is intended to explore in depth various data and information accurately and explain or explain in more depth the subject matter discussed in accordance with the research objectives. The results of the study indicate that the political education for the people in the Direct Local Election of Kampar Regency in 2017, which was carried out by the KPU of Kampar Regency, has been structured in accordance with the existing rules namely Election law and other rules, including the decision of the KPU of Kampar Regency. Political education that has been carried out so far is more structurally socialized, ranging from political education to the voters to community leaders and women. The obstacles faced in the implementation of the Kampar Regency Direct Local Election political education in 2017, namely geographical factors, limited budgets, community enthusiasm and limited personnel or human resources.